THE INFLUENCE OF SITUATIONAL LEADERSHIP STYLE ON THE PERFORMANCE OF EMPLOYEES AT THE SOUTH PALU DISTRICT OFFICE - Juan Fernando Sumampouw; Kornelius, Yoberth; Indriani Ibrahim, Andi; Palawa, Muh. Riswandi (JURNAL MANAJEMEN MOTIVASI, 2026)
This study aims to analyze the influence of situational leadership styles Telling, Selling, Participating, and Delegating on employee performance at the South Palu District Office. A quantitative approach was employed, with data collected through observation and questionnaires from 34 employees. Regression analysis results indicate that all four leadership styles have a positive and significant effect on employee performance. These findings imply the importance of leadership flexibility in adapting styles to employee characteristics to improve work effectiveness and public service quality. Keywords: Situational Leadership, Telling, Selling, Participating, Delegating, Employee Performance, Public Service, Leadership Flexibility